Best Regional Selection Decision Support System for Shallots in Waru District, Pamekasan Regency Using Topsis Method - Fathorrozi Ariyanto; Rofiuddin (Fakultas Teknik Universitas Bhayangkara, 2020)
The location of an area greatly influences the agricultural sector, including the Waru Subdistrict, Pamekasan Regency, a geographical condition that incidentally consists of hilly plains or highlands. So it is very influential on food plants that can be developed in the area. The objective to be achieved in this final project is to make a Decision Support System application for the Best Shallot Producing Region in Waru Subdistrict, Pamekasan Regency Using the TOPSIS Method. From the results of the study it can be concluded that the application system that has been made is running well and quite User Friendly, from the five villages in the Waru sub-district which were used as experimental data, it can be concluded that the selection of the best village using the TOPSIS method recommended for shallot cultivation is Sanah Laok village. with the highest score is 0.6312.